Immune modulation of the tumour microenvironment - Angell, Helen K. (2012)
Regulatory T cells (Tregs) are a distinct lymphocyte lineage, functionally defined as T cells that inhibit an immune response, which is crucial for maintaining peripheral tolerance and the prevention of autoimmunity. Tregs have been implicated in tumour immune evasion, suppressing the anti-tumour immune response, resulting in tumour progression. The aim of this PhD was to recognise how Tregs function and understand how they are able to modulate tumour immunology. In order to research their proposed role in cancer, it was necessary to be able to phenotype, sort and expand functional Tregs. In preliminary research, strategies were designed to phenotype and test the functionality of ex vivo Tregs and commercial isolation kits were tested and compared in terms of cost efficiency and effectiveness. The mechanisms of Treg-mediated suppression were investigated, including the necessity for cell-to-cell contact and the involvement of key cytokines. The importance of particular cytokines in Treg-mediated suppression was not clear; but cell contact appears to be required for optimal suppression.